Comparative study of saline infusion sonography and hysteroscopy for evaluation of uterine cavity in abnormal uterine bleeding - Nallapati, Sowjanya; Pallavee, P.; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intra-cavitary uterine pathology is the commonest cause of abnormal uterine bleeding. Hysteroscopy is considered as the gold standard for uterine cavity examination. However, in resource limited set-ups saline infusion sonography is an effective alternative to hysteroscopy. The current study aims to compare the accuracy of saline infusion sonography with hysteroscopy in identifying intra-cavitary lesions in women with abnormal uterine bleeding. Methods: 52 patients with abnormal uterine bleeding underwent saline infusion sonography followed by hysteroscopy. The parameters studied were endometrial thickness, presence of sub-mucosal fibroid and endometrial polyp. Results: Upon comparison of saline infusion sonography with hysteroscopy, for detecting endometrial hyperplasia the sensitivity, specificity, positive and negative predictive value were 100%, 94%, 40% and 100% respectively. For endometrial polyp the sensitivity, specificity, positive and negative predictive values were 90.90%, 92.68%, 76.92% and 97.43% respectively. Similarly, the sensitivity, specificity, positive and negative predictive values for sub-mucosal fibroid were 86.36%, 83%, 79.16 % and 89.28% respectively. Conclusions: Saline infusion sonography is a less invasive alternative to hysteroscopy for diagnosis of intra-cavitary lesions in women with abnormal uterine bleeding.